2010
DOI: 10.1007/s12223-010-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antimicrobial activity of 4-(β-d-glucopyranosyl-1→4-α-l-rhamnopyranosyloxy)-benzyl thiocarboxamide; a novel bioactive compound from Moringa oleifera seed extract

Abstract: Antimicrobial activity of crude seed extract of Moringa oleifera was investigated by thin layer chromatography bioassay against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Cladosporium cladosporioides, and Penicillium sclerotigenum; most of them were prominently inhibited by an isolate with R(F) 0.92-0.96. Characterization and identification of the extract revealed the occurrence of three bioactive compounds: 4-(α-L-rhamnopyranosyloxy)benzyl isothiocyanate, methyl N-4-(α-L-rhamnopyranosylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…The seeds can be eaten as such green and roasted; powdered and soaked seeds are used for tea as well as in curries (Anwar et al, 2006). The seeds have powerful coagulative and anti-microbial properties on pathogenic strains of Escherichia coli, Pseudomonas aeruginosa, Streptococcus faecalis, Salmonella typhi and Shigella dysenteriae (Oluduro et al, 2010). Important bioactive compounds present in the moringa seeds have been used for anti-microbial, antigenotoxic, anti-inflammatory and anti-tumour promoting activities (Prabhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds can be eaten as such green and roasted; powdered and soaked seeds are used for tea as well as in curries (Anwar et al, 2006). The seeds have powerful coagulative and anti-microbial properties on pathogenic strains of Escherichia coli, Pseudomonas aeruginosa, Streptococcus faecalis, Salmonella typhi and Shigella dysenteriae (Oluduro et al, 2010). Important bioactive compounds present in the moringa seeds have been used for anti-microbial, antigenotoxic, anti-inflammatory and anti-tumour promoting activities (Prabhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Marumoside A, the aglycone moiety is structurally related to potential antiinflammatory active Capsaicin and hydroxyphenylacetamides, the bioactivity of these compounds strictly depend on the fatty amine moiety. In the present study, the antiinflammatory activities of all the synthesized compounds (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) were tested and the inhibition of TNF-α and IL-1β secretion as a measure of anti-inflammatory activity was monitored. The data to this regard are presented in Tables 2 and 3. Antioxidant activity: Marumoside A and its synthesized derivatives were tested for the DPPH free radical scavenging activity (see Table 4).…”
Section: Biology: Antiinflammatory Activitymentioning
confidence: 99%
“…tumor, antiinflammatory, antimicrobial, antioxidant and antihypertensive activities 11,[13][14][15][16][17] . Recently, Marumoside A and other compounds were isolated from the leaves of Moringa oleifera of Thai origin 18 .…”
mentioning
confidence: 99%
“…Moringa oleifera Lam, is a species belonging to the Moringa Branch and Moringaceae family, widely distributed intropical and subtropical regions of Asia, Africa [1] .The whole plant has edible value and can be useful [2] .Its roots, stems, leaves, flowers, seeds, branches and barks are rich in nutrients and medicinal ingredients [3] . Studies have shown that Moringa leaves are rich in potassium, calcium, phosphorus, iron, and essential amino acids, and having antioxidant activity of vitamin C, flavonoids and polyphenols substances [3] .…”
Section: Introductionmentioning
confidence: 99%